2021
DOI: 10.1001/jamapediatrics.2021.0131
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preterm Birth With Long-term Risk of Heart Failure Into Adulthood

Abstract: IMPORTANCE Preterm birth has been associated with increased risk of heart failure (HF) early in life, but its association with new-onset HF in adulthood appears to be unknown. OBJECTIVE To determine whether preterm birth is associated with increased risk of HF from childhood into mid-adulthood in a large population-based cohort. DESIGN, SETTING, AND PARTICIPANTS This national cohort study was conducted in Sweden with data from 1973 through 2015. All singleton live births in Sweden during 1973 through 2014 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 50 publications
0
67
2
Order By: Relevance
“…Recent studies have shown that respiratory (Lovering et al 2013(Lovering et al , 2014Duke et al 2014Duke et al , 2018Molgat-Seon et al 2019), cardiopulmonary (Laurie et al 2018;Goss et al 2018;Mulchrone et al 2020) and cardiovascular (Lewandowski et al 2013b;Huckstep et al 2018Huckstep et al , 2020, impairments persist into adulthood for preterms. These lead to high risk for early onset of chronic obstructive pulmonary disease (COPD), congestive heart failure, pulmonary hypertension and systemic vascular disease in adulthood (Carr et al 2017;Goss et al 2018;Crump et al 2019bCrump et al , 2019aCrump et al , 2020Crump et al , 2021Mulchrone et al 2020). In Table 1 we outline these known and unknown impairments that could or do contribute to a lesser aerobic exercise capacity in adults born preterm.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that respiratory (Lovering et al 2013(Lovering et al , 2014Duke et al 2014Duke et al , 2018Molgat-Seon et al 2019), cardiopulmonary (Laurie et al 2018;Goss et al 2018;Mulchrone et al 2020) and cardiovascular (Lewandowski et al 2013b;Huckstep et al 2018Huckstep et al , 2020, impairments persist into adulthood for preterms. These lead to high risk for early onset of chronic obstructive pulmonary disease (COPD), congestive heart failure, pulmonary hypertension and systemic vascular disease in adulthood (Carr et al 2017;Goss et al 2018;Crump et al 2019bCrump et al , 2019aCrump et al , 2020Crump et al , 2021Mulchrone et al 2020). In Table 1 we outline these known and unknown impairments that could or do contribute to a lesser aerobic exercise capacity in adults born preterm.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth (<37 gestational weeks) affects >10% of live births worldwide ( 1 ) and abruptly interrupts the trajectory of cardiac development, leading to neonatal ( 2 ) and long-term ( 3 ) morbidity. Large-scale birth registries investigating the impact of being born preterm have shown an increased risk for cardiovascular diseases by childhood and adulthood, including heart failure ( 4 , 5 ), ischemic heart disease ( 6 ), and early cardiovascular-related mortality ( 7 ).…”
mentioning
confidence: 99%
“…with term newborns. 4,5 It is imperative to identify the essential risk factors for preterm birth and to enhance perinatal and neonatal management.…”
Section: + Supplemental Contentmentioning
confidence: 99%